2012
DOI: 10.1007/s10461-012-0385-9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of MSM Stigma, HIV Stigma and Depression in HIV-Positive Latino and African American Men who have Sex with Men (MSM)

Abstract: Little research has examined differences in HIV stigma versus MSM stigma and the role of these stigmas in depression for HIV-positive Latino and African American men who have sex with men (MSM), subgroups disproportionately impacted by HIV in the US. MSM stigma, HIV stigma, depression, stress and social support were examined among HIV-positive Latino (n = 100) and African American (n = 99) MSM patients at five HIV clinics in Los Angeles County, California. In multiple regression models, Latino MSM had higher H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 32 publications
4
68
0
1
Order By: Relevance
“…Voluntary HIV testing and use of HIV prevention services often involve the disclosure of stigmatized sexual behavior, such as having same-sex, anonymous, or multiple sexual partners [114116], which can also impede BMSM from using these services [58, 110]. If BMSM are HIV-positive or perceived to be HIV-positive, they may also experience stigma due to HIV status [101, 117121], sometimes leading to a fear of diagnosis and further hindering the use of prevention services [58]. Additionally, Blacks are more disapproving of homosexuality than Whites, even after controlling for religious and educational differences, which promotes internalized homophobia and may inhibit BMSM from adopting HIV testing behaviors [122124].…”
Section: Resultsmentioning
confidence: 99%
“…Voluntary HIV testing and use of HIV prevention services often involve the disclosure of stigmatized sexual behavior, such as having same-sex, anonymous, or multiple sexual partners [114116], which can also impede BMSM from using these services [58, 110]. If BMSM are HIV-positive or perceived to be HIV-positive, they may also experience stigma due to HIV status [101, 117121], sometimes leading to a fear of diagnosis and further hindering the use of prevention services [58]. Additionally, Blacks are more disapproving of homosexuality than Whites, even after controlling for religious and educational differences, which promotes internalized homophobia and may inhibit BMSM from adopting HIV testing behaviors [122124].…”
Section: Resultsmentioning
confidence: 99%
“…Stigma and depression have been shown to be associated in a variety of settings (Simbayi et al 2007; Thi et al 2008; Wu et al 2008; Li et al 2009; Kingori et al 2012; Wohl et al 2012; Logie et al 2013). Since the current study was cross-sectional, we could not assess the temporality of the relationship between depression and sex work-related stigma.…”
Section: Discussionmentioning
confidence: 99%
“…MSM studies that recruit based on self-reported current or recent sex with men, may exclude men who report current sexual relationships with females, but do not self-report a lifetime history of sex with men. Therefore, these studies fail to capture the contextual history associated with men who may be classified as MSM, but in fact may fit under the classification of MSMW (Wilton et al, 2009; Wohl et al, 2012). …”
Section: Introductionmentioning
confidence: 99%